Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1002/syn.21584
|View full text |Cite
|
Sign up to set email alerts
|

Detection of ischemic neuronal damage with [18F]BMS‐747158‐02, a mitochondrial complex‐1 positron emission tomography ligand: Small animal PET study in rat brain

Abstract: The acute and subacute ischemic neuronal damage in rat brain caused by photochemically induced thrombosis (PIT) was imaged using [¹⁸F]BMS-747158-02 ([¹⁸F]BMS) for mitochondrial complex-1 (MC-1) and [¹¹C](R)-PK11195 ([¹¹C](R)-PK) for peripheral benzodiazepine receptor [PBR; translocator protein] at preischemic "Normal," 1 (day 1), and 7 days (day 7) after ischemic insult. When [¹⁸F]BMS was intravenously injected into "Normal" rat, it was rapidly taken up into the brain, in which it showed a homogeneous distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…18 F-BMS is selectively taken up into the heart because of the high density of mitochondria in the cardiac muscle. There are some reports that uptake of MC-1 probes, including 18 F-BMS, was inhibited by pre-injection of rotenone, a MC-1 inhibitor not only in the heart but also in the brain [ 21 , 22 ]. In the present study, hepatic uptake of 18 F-BMS was also reduced by pre-injection of rotenone, indicating that 18 F-BMS is bound to MC-1 in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…18 F-BMS is selectively taken up into the heart because of the high density of mitochondria in the cardiac muscle. There are some reports that uptake of MC-1 probes, including 18 F-BMS, was inhibited by pre-injection of rotenone, a MC-1 inhibitor not only in the heart but also in the brain [ 21 , 22 ]. In the present study, hepatic uptake of 18 F-BMS was also reduced by pre-injection of rotenone, indicating that 18 F-BMS is bound to MC-1 in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we prepared a PET probe specific for MC-I activity to visualize the ischemic brain damage from the acute through subacute phase, and to evaluate the therapeutic effect of FK506-liposomes on cerebral I/R injury. It has been reported that unexpectedly high [ 18 F]FDG uptake and apparent intense staining with TTC are observable in the damaged region at the subacute phase after cerebral I/R in spite of the neurodegenerative death in the area 16 . This phenomenon results from the exclusive production of ATP by activated inflammatory cells such as microglia and macrophages via enhanced glycolysis, the metabolic pathway with a low contribution of the electron transport chain for ATP production 17 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Whether the increased metabolism in the periinfarct zone was purely due to increased metabolic demand from neurons or a combination of neuronal activity and glial proliferation remains unclear, however together with the presence of neuroinflammation it is likely to indicate an increased risk to secondary inflammatory damage for the brain tissue in this area. Fukumoto et al [45,46] further investigated, in two multi-tracer studies, using [ 11 C]-(R)-PK11195 and [ 11 C]flumazenil for central benzodiazepine receptor (CBR) and [ 18 F]FDG for glucose metabolism [45] or [ 18 F]BMS-747158-02 (Mitochondrial Complex-1 ligand) [46], the time-course and localisation of TSPO expression after permanent stroke (photothrombotic model). These authors found that [ 11 C]-(R)-PK11195 uptake matched in localisation the hypermetabolism detected in the periinfarcted area by [ 18 F]FDG, whereas a decrease in [ 18 F]flumazenil [45] and [ 18 F]BMS-747158-02 [46] uptake could be detected in the infarct core.…”
Section: Permanent Ischemiamentioning
confidence: 99%
“…Fukumoto et al [45,46] further investigated, in two multi-tracer studies, using [ 11 C]-(R)-PK11195 and [ 11 C]flumazenil for central benzodiazepine receptor (CBR) and [ 18 F]FDG for glucose metabolism [45] or [ 18 F]BMS-747158-02 (Mitochondrial Complex-1 ligand) [46], the time-course and localisation of TSPO expression after permanent stroke (photothrombotic model). These authors found that [ 11 C]-(R)-PK11195 uptake matched in localisation the hypermetabolism detected in the periinfarcted area by [ 18 F]FDG, whereas a decrease in [ 18 F]flumazenil [45] and [ 18 F]BMS-747158-02 [46] uptake could be detected in the infarct core. In term of time-course, they showed that TSPO expression was low 1 day post-stroke [46] and increases progressively to peak around day 7 post-ischemia and decrease thereafter (day 14) [45].…”
Section: Permanent Ischemiamentioning
confidence: 99%